KAJIAN YURIDIS KEBIJAKAN ANGGARAN PENETAPAN DAN PENEGASAN BATAS DESA - Zendrato, Oktafiani; Silvanti, Amelia; Sitorus, Pandapotan; Silalahi, Nasib Buha; Yamani, M. (LPPM Universitas Bina Bangsa, 2025)
Of the 81,616 villages registered with the Indonesian Central Bureau of Statistics, only a small number have clear and clear village boundaries, and are legal according to current legislation, namely the Regulation of the Minister of Home Affairs (Permendagri) Number 45 of 2016 concerning Guidelines for Determining and Affirming Village Boundaries. The reason why a village does not yet have village boundaries is due to various obstacles, one of which is cost. The determination and affirmation of village boundaries is necessary to ensure the management of areas and resources that are guidelines for effective development planning with efforts to optimize benefits and minimize risks arising from development activities. Since the enactment of the Law on Regional Government. Law on Villages, the administrative boundaries have become very high in urgency. For this reason, the determination and affirmation of village boundaries is very necessary to avoid things that cause disputes between regions and facilitate the administrative system, especially to determine the name of the area occupied by a person as one of the identities of the place. The purpose of this research is to find out how the determination and affirmation of village boundaries and what are the obstacles of each village government in determining the boundaries of their respective villages. So the method used in this writing is a normative method that refers to juridical studies and books and other readings as secondary literature used in determining the answer to the problem